Local injection of infliximab into calcinosis lesions in patients with juvenile dermatomyositis (JDM): a clinical trial - Reza Shiari; Mitra Khalili; Vahide Zeinali; Niloufar Shashaani; Mohammad Samami; Foroughossadat Hosseini Moghaddamemami (BMC, 2024)
Abstract Background Juvenile Dermatomyositis (JDM) is a rare autoimmune disorder that primarily affects muscles and skin. One of the severe complications associated with JDM is calcinosis, and treating this condition presents significant challenges. This study aimed to evaluate the efficacy and safety of local injection of infliximab into calcinosis lesions in patients with JDM. Methods In this clinical trial, five patients diagnosed with JDM and calcinosis lesions were enrolled. The primary treatment consisted of weekly infliximab injections for 16 weeks, targeting all four sides of each lesion. Lesion dimensions, including length and width, were documented and monitored weekly. Before the intervention, patients underwent radiographic imaging. After the final injection in week 16, a follow-up radiographic assessment was performed. Data were analyzed using the Generalized Estimating Equation (GEE) method. Results The lesions' size significantly decreased in both length and width during each visit. On average, the lesion length reduced by 2.66%, and the width shrank by 3.32% per visit. Based on radiographic findings, the average length and width of lesions at the initial visit were 12.09 ± 5.05 mm (range: 6.00-25.50 mm) and 6.35 ± 3.00 mm (range: 2.00-16.00 mm), respectively. The average length and width at the last visit were 5.59 ± 7.05 mm (range: 0-23.00 mm) and 3.41 ± 4.05 mm (range: 0-13.00 mm), respectively. No specific side effects related to the treatment were reported. Conclusions The results suggest that the direct administration of infliximab into the calcinosis lesions of patients with JDM could be a safe and effective treatment approach. Trial registration Name of the registry: The effect of infliximab injection into calcinosis lesions on patients with juvenile dermatomyositis (JDM), Trial registration number: IRCT20210808052107N1, Registration date: 2022-07-22, URL of trial registry record: https://en.irct.ir/trial/58329 .